Effect of supplementation with distillery grains and day confinement on the productive performance of Hereford steers, which graze forage sorghum (Sorghum, spp.) during the summer - Casanova, Dainelis; Beretta, Virginia; Saravia, Celmira; Betancur, O.; Tagliani, E. M.; Taño, M.; Simeone, A. (Cuban Journal of Agricultural Science, 2023)
In the West Coast of Uruguay, on six ha of forage sorghum, the effect of supplementation with more soluble dry distillery grains and day confinement with shade was evaluated on the productive performance of Hereford steers, which graze forage sorghum. A total of forty-eight steers (267 ± 29.5 kg) were randomly assigned to four treatments in a 2 x 2 factorial arrangement: free grazing without supplement, free grazing with supplement, day confinement without supplement, day confinement with supplement (n=2. 6 steers/repetition). It was grazed in weekly strips, with allocation of 8 kg of dry matter of grass/100 kg of live weight. Between 10:00 a.m. and 4:00 p.m., the animals with day confinement were moved from the grass to a near pen, provided with water and artificial shade. The supplementation with more soluble dry distillery grains improved productive performance, regardless of grazing management. Supplementation increased dry matter intake and increased live weight gain 2.9 times, with a weight gain response of 0.928 kg/d and supplement conversion efficiency of 3.1:1 (supplement intake, kg/response in LW gain, kg). The day confinement improved the thermal welfare of animals and did not affect the intake of dry matter or grazing activity. However, it was not enough to express improvements in mean daily gain. Key words: steers, supplementation, more soluble dry distillery grains, day confinement.